The paths to carbon neutrality in the Russian electric power industry - N. G. Lyubimova (Вестник университета, 2022)
The Paris Climate Agreement has endorsed a strategic course towards “carbon neutrality” by 2050. Currently, all or at least most of the anthropogenic CO2 emission in Russia is absorbed by forests. The main sources of CO2 emission are fuel and energy sectors, including the electric power industry and transport. The introduction of a “carbon” tax can cause big losses for Russian manufacturers. To reduce the carbon intensity of electricity production and maintain “carbon neutrality” in the future Russia has to increase generation at nuclear, hydroelectric and other renewable energy sources, take measures to improve the fuel combustion efficiency at coal-fired power plants and introduce more economical gas turbine and combined cycle equipment installations at gas power plants.